2016
DOI: 10.1039/c6ta03788g
|View full text |Cite
|
Sign up to set email alerts
|

An electrodeposited cobalt–selenide-based film as an efficient bifunctional electrocatalyst for full water splitting

Abstract: An amorphous cobalt–cobalt oxide/cobalt selenide composite film has been fabricated directly on a 3D macro-porous Ni foam substrate by a facile electrodeposition method, which can be an efficient and cheap bifunctional electrocatalyst for both the OER and HER and offer potential applications in the field of full water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 59 publications
3
81
0
Order By: Relevance
“…The catalytic activity of metal phosphide/chalcogenide‐based catalysts are mainly attributed to the proper surface of proton acceptor and hydride acceptor sites, leading to moderate bonding between sulphur/selenium/ phosphorus and reaction intermediates in the process of water splitting . Many efforts to fabricate these metal chalcogenide/phosphide based Janus electrodes have been made toward directly growing electrocatalysts on current collectors through hydrothermal deposition, electrodeposition, and chemical vapor deposition . Among them, the design of foam‐based bifunctional electrocatalysts were mainly concentrated on directly in situ synthesis of Ni x M y (M=S, Se, P) on the surface of foams (Ni or Cu foam) also acting as Ni or Cu source by one‐step hydrothermal process or CVD treatment.…”
Section: Water Splittingmentioning
confidence: 99%
“…The catalytic activity of metal phosphide/chalcogenide‐based catalysts are mainly attributed to the proper surface of proton acceptor and hydride acceptor sites, leading to moderate bonding between sulphur/selenium/ phosphorus and reaction intermediates in the process of water splitting . Many efforts to fabricate these metal chalcogenide/phosphide based Janus electrodes have been made toward directly growing electrocatalysts on current collectors through hydrothermal deposition, electrodeposition, and chemical vapor deposition . Among them, the design of foam‐based bifunctional electrocatalysts were mainly concentrated on directly in situ synthesis of Ni x M y (M=S, Se, P) on the surface of foams (Ni or Cu foam) also acting as Ni or Cu source by one‐step hydrothermal process or CVD treatment.…”
Section: Water Splittingmentioning
confidence: 99%
“…In order to develop highly efficient HER electrocatalysts, research in the field has been mostly focused on nanostructured materials with a large number of active sites and highly conductive supporting materials . To maximize hydrophilicity and active site exposure, many works have focused on the growth of nanowires, nanobelts, and nanosheets on the conductive substrates such as carbon fiber and Ti foil . The synthesis methods of these previously reported hydrogen evolution catalysts were mostly limited to the hydrothermal method and electrodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it remains a challenge to develop cobalt‐selenide‐based bifunctional catalysts for OER and HER for overall water splitting. It is reported that the bifunctional Co‐based selenides catalysts, such as cobalt‐selenide‐based film (CoO x —CoSe) and amorphous CoSe film (α‐CoSe/Ti), can be synthesized using energy‐consuming electrodeposition techniques. Moreover, the synthesized catalyst materials, such as CoSe 2 /carbon fiber, CoSe 2 and NiSe 2 nanocrystals, and amorphous Co 2 B grown on CoSe 2 nanosheets (Co 2 B/CoSe 2 ), show the bifunctional activity, but unfortunately they also have high overpotentials for both OER and HER.…”
Section: Introductionmentioning
confidence: 99%